1992
DOI: 10.1515/bchm3.1992.373.2.595
|View full text |Cite
|
Sign up to set email alerts
|

Cystatins and Cathepsins in Breast Carcinoma

Abstract: The increased expression of proteolytic systems is one of the characteristics of transformed and malignant cells and their evaluations in whole tumor homogenates were considered as possible diagnostic and/or prognostic factors. Abnormal intracellular distribution, increased activities and secretion of cysteine proteinases (CPs) cathepsin B (Cat B) and L (Cat L), were associated with tumor progression. In the present study of matched pairs of breast carcinoma and normal breast tissue, the activities of Cat B an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…While one report showed increased levels of serum cystatin C in HNC patients when compared to healthy controls [35], suggesting a pathological role of cystatin C in HNC, another investigation demonstrated that high levels of cystatin C in tumor tissue had a protective effect, being associated with prolonged survival [32]. Similar results were published for breast [15,16] and lung cancer [11].…”
Section: Discussionmentioning
confidence: 68%
“…While one report showed increased levels of serum cystatin C in HNC patients when compared to healthy controls [35], suggesting a pathological role of cystatin C in HNC, another investigation demonstrated that high levels of cystatin C in tumor tissue had a protective effect, being associated with prolonged survival [32]. Similar results were published for breast [15,16] and lung cancer [11].…”
Section: Discussionmentioning
confidence: 68%
“…Beside lung carcinoma [13], increased levels of Cathepsin have also been found in breast carcinoma [14,15], colon carcinoma [16], head and neck carcinoma [17], oesophageal carcinoma [18] and glioma [19,20] as well as in the sera of tumor patients [19][20][21][22][23][24]. Moreover, the enzyme activity of Cathepsin B was 4.5-fold higher in lung tumor tissue compared with lung parenchyma [7].…”
Section: Discussionmentioning
confidence: 99%
“…More compelling evidence demonstrated continual decrease in the level of stefin A mRNA during the progression of murine skin papillomas to carcinoma (12). Similarly, decreased stefin A transcripts were observed in 4 of 5 breast carcinomas as compared to matched normal breast tissues (13). In addition to decreased amounts of stefin A in malignant tissues, Lah and coworkers (14,15) have shown that stefin A, isolated from human sarcoma tissue, has an altered inhibitory activity, being less effective than normal stefin A in inhibiting the proteolytic activity of both papain and cathepsin B. Lastly, we have demonstrated in murine tumors that there is an overall decrease of CPI activity accompanied with an enrichment of the activity within the plasma membrane fraction (16).…”
Section: Introductionmentioning
confidence: 92%